Malvaceae family: fundamental species in agro-food industry with commercial, nutrimental and nutraceutical value - Robles-Valdivia, Miguel Tirso; Sánchez-Otero, María Guadalupe (REVISTA TERRA LATINOAMERICANA, 2022)
The Malvaceae family has species widely distributed worldwide, some of them, such as cotton (Gossypium hirsutum), cacao (Theobroma cacao) and hibiscus (Hibiscus sabdarif fa) are widely used in the agri-food industry and the textile industry; even so, not all the bioactive potential of these species has been exploited, such is the case of H. sabdarif fa, since most of the seeds are considered as agro-industrial waste; there are species of this family, such as some members of the Sterculia and Ceiba genus, that have not been exploited on a massive scale in various industries, despite the fact that there are numerous studies that demonstrate their nutraceutical and medicinal potential.